Een christelijk-wijsgerige benadering van het biologische soortbegrip - Benjamin, Rafael (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2024)
In this article I intend to present a philosophical-biological ground at behalf of the creationistic biology, with a focus on the concept of a biological species. My point of departure is the so called ‘philosophy of the cosmonomic idea’, developed by the Dutch philosopher dr. Herman Dooyeweerd. I try to make it clear, that it is not correct to consider species as things, entities, in the sense of substances. On the basis of the neo-Calvinistic worldview that God has created a cosmic world order of laws that are of a different ontic quality, and that, as Baupläne, as design, hold for all entities, as well as for their different modes of functioning in the world, is it possible to do justice to the meaning diversity and the meaning coherence that we all experience in a pre-theoretical sense. This is something that is not possible when departing from the macro-evolutionistic stance whereby species and entities are considered as substances that are all originated out of each other, because then one entangles himself in a regressus ad infinitum. In that case it is impossible to speak about the concept of a species in the true sense of the word.